The judiciary : the Supreme Court in the governmental process - Abraham, Henry J. (Henry Julian), 1921-2020 (New York University Press, 1996)
Revised and updated to include the latest Supreme Court decisions, this classic text, now in its tenth edition, provides a concise overview of the judiciary in general and the Supreme Court in particular. The only book available that combines theory and practice of the judicial process with civil rights and liberties, The Judiciary acquaints students with the intricacies of our courts, the people who compose them, and their relationship to other branches of government, as well as to individuals and groups.